Difference between revisions of "Math 22 Integration by Parts and Present Value"

From Math Wiki
Jump to navigation Jump to search
 
(6 intermediate revisions by the same user not shown)
Line 3: Line 3:
 
   Let <math>u</math> and <math>v</math> be differentiable functions of <math>x</math>.
 
   Let <math>u</math> and <math>v</math> be differentiable functions of <math>x</math>.
 
    
 
    
   <math>\int u \dv=uv-\int v \du</math>
+
   <math>\int u dv=uv-\int v du</math>
  
 +
'''Exercises''' Use integration by parts to evaluation:
  
 +
'''1)''' <math>\int \ln x dx</math>
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Solution: &nbsp;
 +
|-
 +
|Let <math>u=\ln x</math>, <math>>du=\frac{1}{x}dx</math>
 +
|-
 +
|and <math>dv=dx</math> and <math>v=x</math>
 +
|-
 +
|Then, by integration by parts: <math>\int \ln x dx=x\ln x-\int x\frac{1}{x}dx=x\ln x-\int dx=x\ln x -x +C</math>
 +
|}
  
 +
'''2)''' <math>\int xe^{3x}dx</math>
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Solution: &nbsp;
 +
|-
 +
|Let <math>u=x</math>, <math>du=dx</math>
 +
|-
 +
|and <math>dv=e^{3x}dx</math> and <math>v=\frac{1}{3}e^{3x}</math>
 +
|-
 +
|Then, by integration by parts: <math>\int xe^{3x}dx=x\frac{1}{3}e^{3x} -\int\frac{1}{3}e^{3x} dx=x\frac{1}{3}e^{3x}-\frac{1}{9}e^{3x} +C </math>
 +
|}
  
 +
'''3)''' <math>\int x^2e^{-x}dx</math>
 +
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Solution: &nbsp;
 +
|-
 +
|Let <math>u=x^2</math>, <math>du=2xdx</math>
 +
|-
 +
|and <math>dv=e^{-x}dx</math> and <math>v=-e^{-x}</math>
 +
|-
 +
|Then, by integration by parts: <math>\int x^2e^{-x}dx=x^2(-e^{-x}) -\int-e^{-x}2x dx=-x^2e^{-x}+\int 2xe^{-x}dx </math>
 +
|-
 +
|Now, we apply integration by parts the second time for <math>\int 2xe^{-x}dx</math>
 +
|-
 +
|Let <math>u=2x</math>, <math>du=2dx</math>
 +
|-
 +
|and <math>dv=e^{-x}dx</math> and <math>v=-e^{-x}</math>
 +
|-
 +
|So <math>\int 2xe^{-x}dx=2x(-e^{-x})-\int -e^{-x} 2dx=-2xe^{-x}-e^{-x}+C</math>
 +
|-
 +
|Therefore, <math>\int x^2e^{-x}dx=-x^2e^{-x}-2xe^{-x}-e^{-x}+C</math>
 +
|}
  
 +
==Note==
 +
1. Tabular integration technique (look it up) is convenient in some cases.
  
  

Latest revision as of 16:22, 3 September 2020

Integration by Parts

 Let  and  be differentiable functions of .
 
 

Exercises Use integration by parts to evaluation:

1)

Solution:  
Let ,
and and
Then, by integration by parts:

2)

Solution:  
Let ,
and and
Then, by integration by parts:

3)

Solution:  
Let ,
and and
Then, by integration by parts:
Now, we apply integration by parts the second time for
Let ,
and and
So
Therefore,

Note

1. Tabular integration technique (look it up) is convenient in some cases.


Return to Topics Page

This page were made by Tri Phan